Endogeneous household interaction - Daniela Del Boca; Christopher J. Flinn (Institute for the Study of Labor (IZA), 2009)
Most econometric models of intrahousehold behavior assume that household decision-making is efficient, i.e., utility realizations lie on the Pareto frontier. In this paper we investigate this claim by adding a number of participation constraints to the household allocation problem. Short-run constraints ensure that each spouse obtains a utility level at least equal to what they would realize under (inefficient) Nash equilibrium. Long-run constraints ensure that each spouse obtains a utility level equal to a least what they would realize by cheating on the efficient allocation and receiving Nash equilibrium payoffs in all successive periods. Given household characteristics and the (common) discount factor of the spouses, not all households may be able to attain payoffs on the Pareto frontier. We estimate these models using a Method of Simulated Moments estimator and data from one wave of the Panel Study of Income Dynamics. We find that the model with long-run participation constraint fits the data best, and that 6 percent of sample households are not able to attain efficient outcomes. To meet the long-run participation constraint, over 90 percent of efficient households are required to modify the ex ante Pareto weight of 0.5 for each spouse assumed to apply to all households.
Keywords: C79; D19; J22; 330; Household time allocation; grim trigger strategy; household production; method of simulated moments; Haushaltsökonomik; Zeitallokation; Ehe; Pareto-Optimum; Simulation; Theorie; USA